Epstein-Barr virus (EBV) serology and its impact on oral human papillomavirus (HPV) infection outcomes in children during early childhood - Rinne, Sanni; Michels, Birgitta; Butt, Julia; Syrjänen, Kari; Grenman, Seija; Waterboer, Tim; Syrjänen, Stina; Louvanto, Karolina (American Society for Microbiology, 2026)
Epstein-Barr virus (EBV) and various human papillomaviruses (HPVs) commonly infect the oral mucosa, yet the longitudinal effects of these infections and their potential coinfections remain poorly understood. This study investigated whether early EBV infection and antibody responses influence oral HPV infections in young children. We included 283 children from the Finnish Family HPV cohort study, who were followed for 3 years post-birth. Oral and blood samples were collected at six time points (1, 2, 6, 12, 24, and 36 months). HPV genotyping was performed with Luminex and EBV-IgG antibodies to Zebra, early antigen-diffuse (EA-D), EBV nuclear antigen 1, and viral capsid antigen p18 with fluorescent bead-based multiplex serology. We noticed that most children (91.4%; n = 254) experienced the vanishing of maternal EBV-IgG antibodies within 11.3 months, and by 36 months, 17% (41/238) of the children had developed their own EBV antibodies. Intriguingly, higher paternal education levels were strongly associated with lower EBV seropositivity in children at ages 2 and 3, with an odds ratio(OR) range of 0.06 to 0.16 (95% confidence interval range 0.005–0.91). Additionally, children with the highest baseline titers of EA-D antibodies had 2.5- and threefold risk for incident oral HPV infection and its clearance, respectively. Our findings suggest that EBV seropositivity at 3 years of age is relatively low in our Finnish data, and the level of paternal education was a significant protective factor against early EBV seropositivity. Moreover, the observed association between high EA-D antibody titers and oral HPV infection underscores the need for further research into the complex interactions between EBV and HPV.